O processo de gestão do Parque Municipal Nascentes do Mindu - Lima, Márcio Bentes (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
LIMA, Marcio Bentes. The Management Process of the Nascentes do Mindu Municipal Park. Manaus, 2018. Dissertation (Professional Master in Management of Protected Areas of Amazonia) - National Institute of Amazonian Research - INPA. The main strategy of environmental conservation accepted and adopted today is the creation of protected territorial spaces. Conservation units are legally established areas with principles of protection of their natural resources, presenting themselves as natural sanctuaries, where the environmental quality of the territory is complete, with its ecosystem processes in full operation, or with some degree of threat strategy to ensure its protection. The preservation of biological diversity on the planet depends on the strategies that man will adopt to conserve it, in view of this scenario the establishment of technical, scientific and legal criteria must be integrated for the identification, creation and management of conservation units, so that their objectives to be achieved, use management must be planned efficiently so that environmental conservation objectives are met. This research study analyzed, through the case study, the management processes applied in Nascentes do Mindu Municipal Park, located in the city of Manaus / AM, aiming to understand the strategic actions developed and their management difficulties that could present successful experiences in the management; and how a poor management can compromise its environmental conservation. For the development of the results of academic research, concepts and principles of general domain and bibliographical citations were used, where topics such as the creation of protected areas, their importance for environmental conservation and their strategies and management tools were discussed. After the study of the bibliographic reference, a follow-up of the activities performed and the problems faced by the Park, as well as its management solutions were carried out. It is concluded that it is necessary that the management plan be reviewed, that the management board is an instrument of great relevance for the management, that improvements be made in the managerial aspects, according to suggestions and that more formal institutional partnerships for the protected space are made possible.
Keywords: Unidades de conservação; Proteção Ambiental